Effects of landscape disturbance on the population dynamics and behaviour of moose (Alces alces) in the greater Pukaskwa ecosystem, Ontario - Burrows, Frank G. M. (2001)
I studied the population dynamics, movements and home range of moose {Alces alces) in the Greater Pukaskwa Ecosystem, Ontario, during 1995-1999. My study compared two landscapes experiencing different management regimes: Pukaskwa National Park (PNP), a wilderness park, and the adjacent Wildlife Management Unit #33 (WMU33), a multiuse forest with commercial timber harvest (part of the White River Forest). I hypothesized that because PNP was not disturbed (i.e., by fire or timber harvest) and WMU33 was, the condition of moose and moose habitat carrying capacity would be better in WMU33 than PNP. I used 5 triennial aerial moose surveys to assess population dynamics and distribution, and 35 radio-collared adult female moose to assess productivity, survival, marrow condition, blood condition, morphometries, movements and home range. I found the mean moose density per plot in the most recent aerial surveys to be slightly higher but not statistically different in WMU33 than PNP (0.332 and 0.273 moose/km2, respectively), and kriging demonstrated that most of the high moose densities occurred in WMU33 and were increasing more than in PNP. Survival rates were not significantly different between landscapes (93% in PNP and 89% in WMU33), and were similar to findings of other studies. Marrow fat showed differences among seasons, being highest in summer and lowest in late winter, but was not significantly different between landscapes. Movements in PNP were greater than in WMU33, and PNP moose showed distinct movements between summer and winter ranges, which was not seen in WMU33. Seasonal movements were significant, with summer being the greatest (22.0 m/hr in PNP and 20.1 m/hr in WMU33) and winter the smallest (6.9 m/hr in PNP and 5.5 m/hr in WMU33). Annual MCP home range sizes were significantly larger in PNP than WMU33 (70 and 43 km2, respectively). Home ranges also showed significant season effects, being largest in summer and smallest in winter. In my study, I found that moose occupying the WMU33 landscape have shown a slight positive response to forest disturbance, caused by timber harvest, through increased population density. I did not find statistically important differences in physical condition of moose between the two landscapes, but moose in WMU33 made smaller movements and had smaller home ranges than moose living in the undisturbed landscape of PNP.